Border Irrigation for Gaur in Semi-Arid Zone of Rajasthan - Kumar, Devendra (Annals of Arid Zone, 2016)
This paper deals with the water front advance studies and studies on appli- cation, distribution and water use efficiencies in level border irrigation for guar (Cyamopsis tel Taub.) in semi-arid zone of Rajasthan. A study on border irrigation with different border widths and cut-off ratios was conducted with the stream size of 2.01 second/m width of border. 8 x 50 m2 border gave the higher application and distribution efficiency. This size with 80% cut-off ratio may be adopted In the arid zone of Rajasthan. The regression equations developed in the paper may be used for the efficient design of border in the region, when the stream size is in the range of 8.1/sec to 20.1/sec.